Upodobnienie się do Chrystusa w monastycyzmie wschodnim w okresie patrystycznym – zarys zagadnienia - Żelazny, Jan Witold; Kasprzak, Dariusz Antoni (Vox Patrum, 2025)
The article focuses on the importance of following and following Christ in the context of Eastern patristic monasticism. Authors such as Aphrahat, Anthony the Great, Barsanuphius, John the Prophet and Joseph Hazzaya present a variety of approaches to this topic that have not yet been synthesized in Polish. It seems that the New Testament motif of following (ἀκολουϑεῖν) Jesus is losing its autonomy and original meaning, and sometimes even seems to be disappearing in the ascetic thought of Eastern monasticism of the patristic period. Monks are careful to say that they follow the One who is now in glory, and with whom they identify as Christians, after all. For them, the more significant element of conforming to Jesus is asceticism and living according to the virtues, which are spiritual and moral reflections (μιμεῖσϑαι) of the monk’s conformity to Christ. The motif of conformity to Christ in Eastern monasticism is therefore not anthropologically unified, nor does it form any paradigmatic account for moral theology or Christian spirituality until the 8th century in Eastern theology.